The Effect of Health Education with Flashcard Media on Improvement of Knowledge and Reduction of Anxiety Degree in Adolescents Primigravida - Dwie Yunita Baska; Tita Husnitawati Madjid; Ponpon S. Idjradinata (Universitas Islam Bandung, 2020)
The education about the reproductive health of pregnancy is needed to increase knowledge and reduce anxiety in adolescent primigravida, one of them is by conducting flashcard media. Flashcards are pictorial media in the form of cards that have words; it’s proven to be able to create fun learning, attracts attention, and stimulates critical thinking. The purpose of the study was to analyze the effect of education with flashcard media on knowledge and anxiety degree in adolescent primigravidas. The research method used in this study was a one-group pretest-posttest quasi-experimental design. The number of samples as many as 30 people (<20 years old) at Sawah Lebar Public Health Center and Padang Serai Public Health Center in Bengkulu city from May to July 2018, by using consecutive sampling. The data of this study obtained from pretest and posttest questionnaires of knowledge, and Zung Self-rating Anxiety Scale (ZSAS), Shapiro-Wilk, Wilcoxon, and chi-square test statistics. The results showed a significant increase in knowledge before and after the intervention of p value=0.001 (p<0.05), an increase in the average score of knowledge of series one card amounts to 35.0% and knowledge of series 2–3 card amounted to 30%. A significant decrease in anxiety degree of 9.2% after the treatment (p<0.05). In conclusion, flashcards can increase knowledge and reduce the anxiety of adolescents primigravida mothers so that health workers use this educational approach appropriately. PENGARUH EDUKASI KESEHATAN DENGAN MEDIA FLASHCARD TERHADAP PENINGKATAN PENGETAHUAN DAN PENURUNAN DERAJAT KECEMASAN PADA PRIMIGRAVIDA REMAJAThe education about the reproductive health of pregnancy is needed to increase knowledge and reduce anxiety in adolescent primigravida, one of them is by conducting flashcard media. Flashcards are pictorial media in the form of cards that have words; it’s proven to be able to create fun learning, attracts attention, and stimulates critical thinking. The purpose of the study was to analyze the effect of education with flashcard media on knowledge and anxiety degree in adolescent primigravidas. The research method used in this study was a one-group pretest-posttest quasi-experimental design. The number of samples as many as 30 people (<20 years old) at Sawah Lebar Public Health Center and Padang Serai Public Health Center in Bengkulu city from May to July 2018, by using consecutive sampling. The data of this study obtained from pretest and posttest questionnaires of knowledge, and Zung Self-rating Anxiety Scale (ZSAS), Shapiro-Wilk, Wilcoxon, and chi-square test statistics. The results showed a significant increase in knowledge before and after the intervention of p value=0.001 (p<0.05), an increase in the average score of knowledge of series one card amounts to 35.0% and knowledge of series 2–3 card amounted to 30%. A significant decrease in anxiety degree of 9,2% after the treatment (p<0.05). In conclusion, flashcards can increase knowledge and reduce the anxiety of adolescents primigravida mothers so that health workers use this educational approach appropriately.